H02 Parental perspectives of early adolescent neighbourhood outdoor play and physical activity: barriers and facilitators - Cox, Lindsay; Wilson, Helen (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Introduction: Outdoor neighbourhood play supports physiological and psychological health among early adolescents (EA), typically aged 10-14. Existing research is often grounded in socioecological theory emphasising the interconnectedness of individuals and their environments. It has also typically focused on parental perspectives of facilitators and barriers of neighbourhood play in younger children. Aims: This study aimed to ascertain facilitators and barriers of outdoor neighbourhood play as perceived by EA parents. Methods: A purposive sample (n=11) of parents engaged in individual semi-structured interviews online via Microsoft Teams. Transcripts underwent reflexive inductive thematic analysis, identifying six themes aligned with the research question within a socioecological framework. Results: Most parents (n=10) demonstrated an awareness and appreciation of the advantages of outdoor neighbourhood play. They identified barriers and facilitators to outdoor neighbourhood play across intrapersonal, interpersonal, community and policy levels. Safety concerns emerged as a barrier to outdoor play. However, technology mediated reported concerns and was perceived as a facilitator to outdoor play when combined with age-appropriate community clubs and improved built environment facilities. Conclusion: Parents acknowledged the advantages of outdoor neighbourhood play. Parents may restrict their EA’s participation due to safety concerns. The study highlighted a deficiency in age-appropriate facilities supporting safe outdoor neighbourhood play. Future research should focus on developing appropriate facilities and improving social cohesion to mitigate perceived safety concerns of parents. Such attempts may benefit from using technology to assuage parental safety concerns further and enhance overall safety of neighbourhood outdoor play experiences for EA.